Process Improvement and Economic and Environmental Evaluation of Bio-Hydrogenated Diesel Production from Refined Bleached Deodorized Palm Oil - Amata Anantpinijwatna; Lida Simasatitkul; Kanokporn Yooyen; Suksun Amornraksa; Suttichai Assabumrungrat; Karittha Im-orb (My University, 2025)
The co-production of BHD with other renewable fuels (i.e., using a novel process involving carbon dioxide utilization to achieve the global sustainability goal) is presented. The three configurations of BHD production from refined bleached deodorized palm oil (RBDPO), including (1) the conventional BHD process with hydrogen recovery (BHD process), (2) the BHD process coupled with the Fischer–Tropsch process (BHD-FT process), and (3) the BHD process coupled with the bio-jet fuel and methanol processes (BHD-BIOJET-MEOH process) are investigated using the process model developed in Aspen Plus. The effect of the operating parameters is studied, and the condition of each process offering the highest BHD yield is proposed. Then, the pinch analysis and heat exchanger network (HEN) design of each proposed process are performed to find the highest energy-efficient configuration. The economic and environmental analysis is later performed to investigate the sustainability performance of each configuration. The conventional BHD process requires less hydrogen and consumes less energy than the others. The BHD-BIOJET-MEOH process is the most economically feasible, offering the highest net present value (NPV) of USD 7.93 million and the shortest payback period of 3 years and 1 month. However, it offers the highest carbon footprint of 0.820 kgCO2 eq./kg of BHD, and it presented the highest potential environmental impact (PEI) in all categories.
Keywords: Biodiesel Production and Applications